A Portrait of Teacher Training Program for Tutors in Tuition Center in Indonesia - Ramadhani, Dwi Putri; Sumaryanto Florentinus, Totok; Utanto, Yuli (Universitas Negeri Semarang, 2021)
Teacher training is a group of several activities conducted intentionally by a group of people or someone using many kinds of learning type to enhance capability, knowledge, experience and action to create meaningful learning. The aim of this study is to describe teacher training in tuition center. The method applied in this study is explanatory mixed method by Creswell. Data collection technique used are questionnaire, interview, observation and applied parametric inferential data for numerical data. The research result showed that even though tutors in tuition center are not from educational program, they still have high interest to teach. The existed training system is proven to be effective to teach pedagogical knowledge for tutors with non educational program. Training program for tutors are not systematic yet, therefore there is a huge oportunity and challenge for curriculum developer to create a curriculum for tutors in tuition center that can be use by all tuition center in Indonesia. This study proved that there is an urgent need of curriculum for teacher training program in tuition center and also become a reference to develop the curriculum. This study can be used as a reference for curriculum developer to create curriculum for tutors in tuition center.